Status Kerusakan Tanah Pada Berbagai Penggunaan Lahan Di DAS Welang Wilayah Tengah Kabupaten Pasuruan - Nailussa'adah, Fina; Maroeto, Maroeto; Purwadi, Purwadi (Jurnal Solum, 2023)
Welang watershed is a watershed located in Pasuruan Regency. Welang watershed has 522.89 km2. Changes that occur in the soil due to uncontrolled use can reduce soil productivity and reduce the main function of the soil. The factor causing soil damage is the increase in population in an area that is not following its function. The measurement of the standard criteria for soil damage refers to the Regulation of the Minister of the Environment No. 07 of 2006. This study aims to assess the status of land use against soil damage. The results showed that the Welang watershed in the central region of Pasuruan Regency had a damaged status, namely lightly damaged (R.I). Redox as a limiting factor in each different land use, namely irrigated rice fields, rainfed rice fields, mixed gardens, dry fields, and forests) in Purwosari and Purwodadi sub-districts. Efforts were made to improve the damage status with redox limiting factors with the addition of organics. The addition of materials is carried out by periodic fertilization for physical, chemical, and biological improvement of the soil.Key words: Damage, Welang Watershed, Land